Prevalence and Contributing Factors of Rhinitis Among a Sample of Medical Students in Baghdad - Haider Majid Haider Al-Zaidi; Mena Subhi Muttashar; Ali Majid Mutrib; Anfal Khalid Hendi; Fatima Ali Majed; Sarah Haider Majid Al-Zaidi (Diyala Journal of Medicine, 2025)
Background: Rhinitis and nasal irritation are highly prevalent, significantly impacting the quality of life for millions of patients. The high prevalence of rhinitis in Iraq may be attributed to environmental factors, including dust storms, pollution, and a poor air quality index. Rhinitis is a group of symptoms that includes congestion, rhinorrhea, sneezing, and nasal itching. Rhinitis can be divided into several groups; however, it typically refers to a group of nasal symptoms. Three primary forms of rhinitis are known: allergic rhinitis (AR), infectious rhinitis, and non-allergic, non-infectious rhinitis (NAR). In certain instances, an overlapping or mixed type may exist, making it essential to refrain from oversimplification. Because of this, it is crucial to be cautious not to oversimplify. Objectives: This study aims to determine the prevalence of rhinitis among a sample of medical students and to identify possible associated factors that may exacerbate this condition. Patients and Methods: A cross-sectional study was conducted at a medical college and a college of dentistry in Baghdad from February 1 to July 1, 2024. It included 600 students randomly selected from these two colleges at all stages of their education. Based on a questionnaire, comprehensive history, and ARIA guidelines, the diagnosis of rhinitis was made. Results: In this study, rhinitis was diagnosed in 29.8% of participants. The most common nasal symptoms were sneezing (55.2%), headache (55%), nasal obstruction (48.8%), and postnasal drip (47.5%). Medical college students and those with a positive family history had the highest prevalence of rhinitis. Conclusion: The prevalence of rhinitis in Iraq is relatively high, similar to findings in the Gulf area. Substantial environmental changes and genetic influence over the past few decades are two potential causes. This study supports recent research indicating that allergic diseases are becoming increasingly prevalent in modern societies. Keywords: Rhinitis, Nasal irritation, University students, Air quality index.